PENGARUH SELF EFFICACY, KECERDASAN EMOSIONAL, TEKANAN KETAATAN DAN KOMPLEKSITAS TUGAS TERHADAP AUDIT JUDGMENT AUDITOR (STUDI EMPIRIS PADA KAP DI PEKANBARU, PADANG DAN BATAM) - -, Suwandi; -, Zulbahridar; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is to analyze the influence of self-efficacy, emotional quotient, obedience pressure and task complexity to auditor’s audit judgment. Using self-efficacy and emotional quotient as the internal factors and obedience pressure and task complexity as the external factors. Self-efficacy refers to the belief that a person has the capacity to organize and execute the course of action required to produce the desired outcome. Emotional Quotient refers to the ability to recognize and control own feeling in any confusing situation, while obedience pressure comes from department/company there were audited or high rank officers and from professional standards. Task complexity is defined as the numerous tasks that come continuously and confusing the auditor. This research used samples of auditor who works in public accountant office in Pekanbaru, Padang and Batam. This research used convenience sampling method. Research tool used questionnaire which was distributed to the auditors directly or by mail as much 80 and only 35 replayed. The analyzed method used in this research is multiple regression analysis by using SPSS (Statistical Product and Service Solution) 17. The result of this research showed that self-efficacy, emotional quotient, obedience pressure and task complexity affect the auditor’s audit judgment.Keywords: self-efficacy, emotional quotient, obedience pressure, task complexity, audit judgment.